Pacemaker Placement in Patients with Stroke-Mediated Autonomic Dysregulation - Ali A. Alsaad; Christopher O. Austin; Maisha T. Robinson; Michael B. Phillips (Case Reports in Medicine)
Lateral medullary syndrome (LMS) is an ischemic disease of the medulla oblongata, which involves the territory of the posterior inferior cerebellar artery. Lateral medullary syndrome is often missed as the cause of autonomic dysregulation in patients with recent brain stem stroke. Due to the location of the baroreceptor regulatory center in the lateral medulla oblongata, patients with LMS occasionally have autonomic dysregulation-associated clinical manifestations. We report a case of LMS-associated autonomic dysregulation. The case presented as sinus arrest and syncope, requiring permanent pacemaker placement. A dual-chamber pacemaker was placed, after failure of conservative measures to alleviate the patient’s symptoms. Our case shows the importance of recognizing LMS as a potential cause for life-threatening arrhythmias, heart block, and symptomatic bradycardia. Placement of permanent pacemaker may be necessary in some patients with LMS presenting with syncope, secondary to sinus arrest.